Prosecuting Crimes of International Concern: Islamic State at the ICC? - Kenny, Cóman (Utrecht Journal of International and European Law, 2017)
The rise of Islamic State (IS) has fundamentally altered the conception of terrorism, a development which international criminal law is arguably unprepared for. Given the scale and gravity of the group’s crimes, questions abound as to how those responsible will be held accountable. In the absence of significant domestic prosecutions and short of the establishment of a dedicated accountability mechanism, the International Criminal Court (ICC) stands as the forum of last resort in which IS members could stand trial. Such a proposition is not without significant challenges, however. This article addresses some key issues facing any potential prosecutions from the perspective of: (i) jurisdiction; (ii) applicable crimes; and (iii) modes of liability. First, as Syria, Iraq, and Libya are not States Parties to the Rome Statute, the available avenues for asserting jurisdiction will be assessed, namely: a Security Council referral; jurisdiction over so called ‘foreign fighters’ who are State Party nationals; and jurisdiction over attacks on the territory of a State Party and whether they could be considered part of a broader series of criminal acts in IS held territory. Second, as there is no crime of terrorism in the Rome Statute, the question of prosecuting acts encapsulated in a systematic campaign of terror through existing provisions will be assessed. Third, the regime of accountability at the ICC will be analysed in light of IS’s purported structure and the crimes with which it stands accused. Focus will be directed to those responsible for the propagation of genocidal propaganda and individuals who provide aid or assistance to IS which contributes to its crimes. These questions are far from theoretical. The UN has designated IS a threat to international peace and security. There follows an expectation that international criminal law should play a role in tackling one of the major criminal concerns of our time and ensure that impunity for those responsible for IS’s atrocities is avoided.